Knobloch Syndrome Type 1 with a Novel Pathogenic Variant in the COL18A1 Gene: Case Report and Review of the Literature - Yaneva Staykova, Slavyana; Atanasoska, Maya; Balabanski, Lubomir; Aleksandrova, Iliyana; Deneva, Daniela; Bozhinova, Veneta; Toncheva, Draga; Vazharova, Radoslava (Journal of Pediatric Neurology, 2024)
Knobloch syndrome type 1 (KNO1) is a rare autosomal recessive disorder characterized by various ocular abnormalities, developmental delay, central nervous system, and urogenital tract abnormalities. KNO1 occurs phenotypically in the presence of at least two pathogenic variants of the COL18A1 gene in biallelic state, regardless of the individual's sex. We describe a novel nonsense variant in the COL18A1 gene, associated with KNO1 in a 2-year-old boy, born of a nonconsanguineous couple. This boy was referred for genetic analysis based on clinical evidence of bilateral frontal polymicrogyria of unknown etiology. Whole-exome sequencing and targeted analysis of genes associated with ataxia, polymicrogyria, and hereditary malformations of the brain was employed. One known pathogenic heterozygous splice acceptor variant (NM_001379500.1:c.929–2A > G) and one likely pathogenic novel nonsense heterozygous variant (NM_001379500.1:c.3083C > A) in the COL18A1 gene were identified. The c.929–2A > G substitution affects the splice acceptor sequence and causes impaired messenger ribonucleic acid (mRNA) maturation. The c.3083C > A variant affects the translated sequence and leads to the formation of a stop codon. Both variants are thought to result in a lack of protein product (as a result of nonsense-mediated mRNA decay) or in the production of truncated nonfunctional protein. KNO1 can go undiagnosed, thus, genetic testing can be a powerful tool for disease detection, specifically in cases in which retinal detachment and occipital encephalocele syndrome are present. Timely diagnosis not only ensures that patients are aware of the potential complications resulting from the condition such as lens subluxation, retinal detachment, and glaucoma, but can help plan appropriate disease prevention and therapy measures in affected families.
Keywords: Knobloch syndrome type 1; COL18A1 gene; retinal detachment; occipital encephalocele syndrome; whole-exome sequencing